Symbolic Attributed Graphs for Attributed Graph Transformation - Orejas, Fernando; Lambers, Leen (Electronic Communications of the EASST, 2010)
In this paper we present a new approach to deal with attributed graphs and attributed graph transformation. This approach is based on working with what we call symbolic graphs, which are graphs labelled with variables together with a formula that constrains the possible values that we may assign to these variables. In particular, in this paper we will compare in detail this new approach with the standard approach to attributed graph transformation.